Revisiting the Syntax–Semantics Interface: Theoretical, Empirical, and Computational Insights - Monteza, Ana Mae M.; Hermansyah, Sam (Indonesian Scientific Publication, 2025)
The syntax–semantics interface has become a central focus in linguistics, as it explains how structural configurations shape meaning and how interpretation constrains syntactic possibilities. This review aims to synthesize theoretical, empirical, computational, and cross-linguistic perspectives to provide a comprehensive account of the interface. Findings indicate that generative and minimalist theories emphasize structural roles, while constructionist and distributional models highlight usage and context. Empirical studies reveal challenges for bilingual and heritage speakers, and computational approaches demonstrate the value of hybrid models bridging theory and data. The review contributes to advancing linguistic theory and practice by underscoring the need for integrative models that combine formal rigor, empirical validation, and cross-linguistic inclusivity.